2022
DOI: 10.3389/fvets.2022.990798
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking calf health: Assessment tools for dairy herd health consultancy based on reference values from 730 German dairies with respect to seasonal, farm type, and herd size effects

Abstract: Good calf health is crucial for a successfully operating farm business and animal welfare on dairy farms. To evaluate calf health on farms and to identify potential problem areas, benchmarking tools can be used by farmers, herd managers, veterinarians, and other advisory persons in the field. However, for calves, benchmarking tools are not yet widely established in practice. This study provides hands-on application for on-farm benchmarking of calf health. Reference values were generated from a large dataset of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that umbilical infections occur in 1.3 to 14% of dairy calves ( 20 , 21 ). According to a recent study, omphalitis is the most commonly detected disorder in pre-weaned calves, with the largest proportion being 15.9% at herd level ( 22 ). Additionally, omphalitis has been found to cause 23% of preslaughter mortality and 54% of post-slaughter in veal calves ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that umbilical infections occur in 1.3 to 14% of dairy calves ( 20 , 21 ). According to a recent study, omphalitis is the most commonly detected disorder in pre-weaned calves, with the largest proportion being 15.9% at herd level ( 22 ). Additionally, omphalitis has been found to cause 23% of preslaughter mortality and 54% of post-slaughter in veal calves ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is growing interest in systems involving prolonged cow-calf contact (see IDF factsheet "Rearing of calves by dam-calf contact" 38/2024), most farms artificially rear calves by feeding milk or milk replacer using controlled feeding practices. Despite evidence supporting calves' ability to consume high quantities of milk, i.e., 20% of a calf's BW [7], and findings showing some farms adopting higher plane of nutrition [8], many calves are still fed approximately 10% BW during the entire milk feeding period (on average <6L/d, [9,10]). Feeding restricted milk allowances, over two to three meals, differs greatly from the natural feeding patterns for calves: in nature calves suckle from the cow frequently throughout the day.…”
Section: Introductionmentioning
confidence: 99%